Implications of sentiments on equity premium : case of Japan and USA - Low, Rachel Zhi Min (2018)
Abel (2002) showed that pessimism and doubt in the subjective distribution of the growth rate of consumption resolved the equity premium puzzle. In this paper, we use the point forecasts of output and consumption data from Japan and USA to uncover possible evidence of pessimism or optimism in these two countries. The differences in the financial systems in Japan and USA aroused our interest to find out the general sentiments on asset returns in these two countries. Subsequently, we provide empirical evidence on the implication of sentiments on asset returns in these two countries from the period 1995 to 2016. We discovered that forecasters from USA’s Survey of Professional Forecasters were generally pessimistic and this outlook increased the average equity premium which may resolve the equity premium puzzle presented by Mehra and Prescott (1985). On the other hand, forecasters from the Japan Cabinet Office were optimistic in their forecast and this had an opposite effect on the average equity premium. Another significant finding is that after taking into account the effect of sentiments, the gap between the equity premium of Japan and USA has narrowed from 3.47% during the period 1975-1995 to 2.44% for the period 1995-2016.